2016
DOI: 10.1016/j.biomaterials.2015.09.035
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analyses to quantify advantages of 2D and 3D hydrogel culture systems in maintaining the native valvular interstitial cell phenotype

Abstract: Valvular interstitial cells (VICs) actively maintain and repair heart valve tissue; however, persistent activation of VICs to a myofibroblast phenotype can lead to aortic stenosis. To better understand and quantify how microenvironmental cues influence VIC phenotype and myofibroblast activation, we compared expression profiles of VICs cultured on poly(ethylene glycol) (PEG) gels to those cultured on tissue culture polystyrene (TCPS), as well as fresh isolates. In general, VICs cultured in hydrogel matrices had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
72
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(80 citation statements)
references
References 54 publications
1
72
1
Order By: Relevance
“…Other approaches for reducing aSMA expression have involved 3D VIC culture in soft hydrogels. 10,[23][24][25] Interestingly, VIC encapsulation in synthetic hydrogels decorated with peptides derived from collagen I led to the lowest percentage of aSMA-positive VICs compared with fibronectinand elastinderived peptides. 23 In many of these cases, the ability to induce the quiescent phenotype has been hypothesized to depend on the soft mechanical properties of these materials.…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches for reducing aSMA expression have involved 3D VIC culture in soft hydrogels. 10,[23][24][25] Interestingly, VIC encapsulation in synthetic hydrogels decorated with peptides derived from collagen I led to the lowest percentage of aSMA-positive VICs compared with fibronectinand elastinderived peptides. 23 In many of these cases, the ability to induce the quiescent phenotype has been hypothesized to depend on the soft mechanical properties of these materials.…”
Section: Discussionmentioning
confidence: 99%
“…Others and we demonstrated that three‐dimensional (3D) matrix‐embedding influences the phenotype and genotype of a variety of human cells mimicking the in vivo cell type to a greater extent than simply 2D tissue culture plating (Baharvand, Hashemi, Kazemi Ashtiani, & Farrokhi, ; Benya & Shaffer, ; Luca et al, ; Mabry, Payne, & Anseth, ; Methe et al, ; Nelson & Bissell, ). 3D cell culture systems have gained increasing interest in drug discovery and tissue engineering due to their evident advantages in providing more physiologically relevant information and more predictive data for in vivo tests (Edmondson, Broglie, Adcock, & Yang, ).…”
Section: Introductionmentioning
confidence: 92%
“…6,33,[37][38][39][40] The amount of fibrillar F-actin in cells cultured on the 2D hydrogels was much lower in both cell lines than on TCPS (Figure 3c). [41][42] Comparing the 2D hydrogels by qualitative visual inspection, we observed that more cells could adhere to the "collagen-rich" substrate over the collagen I only substrate for both MDA-MB-231 and Hs578T cell lines. This result is likely due to the variety of integrin-binding sites provided by the protein mixture.…”
Section: Lap Is An Efficient Photoinitiator To Synthesize 2d Peg-pc Hmentioning
confidence: 99%